BRICS 15 Years On: Challenges and Opportunities for Emerging Countries in the Shifting Global Institutional Landscape - Gabriel Rached; R.M. Rodrigues de Sá (Vestnik MGIMO-Universiteta)
Since the onset of the 2008 financial crisis, the concept of multipolarity has regained prominence, driven by the persistent demands of emerging economies for increased representation and involvement within multilateral institutions. Since 2009, BRICS nations have orchestrated collaborative economic strategies to recalibrate their positions on the global stage. This article seeks to examine the positioning of new entities such as the New Development Bank (NDB) and China-led initiatives within a landscape characterized by the coexistence of traditional structures primarily led by the US and Europe. Against the backdrop of recent global developments, the research endeavors to elucidate the effective role of BRICS in the contemporary international arena, fifteen years since their inception. Specifically, it explores whether current international transformations align with BRICS' aspirations. The investigation employs theoretical frameworks from International Political Economy (IPE), particularly focusing on the dynamics of international multilateral frameworks.